Association of tumor necrosis factor-α and -β gene polymorphisms in inflammatory bowel disease - Al-Meghaiseeb ES; Al-Robayan AA; Al-Otaibi MM; Arfin M; Al-Asmari AK (Dove Medical Press, 2016)
Ebtissam Saleh Al-Meghaiseeb,1 Abdulrahman A Al-Robayan,1 Mulfi Mubarak Al-Otaibi,1 Misbahul Arfin,2 Abdulrahman K Al-Asmari2 1Department of Gastroenterology, 2Research Centre, Prince Sultan Military Medical City, Riyadh, Saudi Arabia Abstract: Inflammatory bowel disease (IBD) is a complex, multifactorial, chronic inflammatory disorder of the gastrointestinal tract in which immune dysregulation caused by genetic and/or environmental factors plays an important role. The aim of this case–control study was to evaluate the association of tumor necrosis factor-alpha (TNF-α) (308) and -β (+252) polymorphisms with susceptibility of IBD. A total of 379 Saudi subjects including 179 IBD patients (ulcerative colitis (UC) =84 and Crohn’s disease (CD) =95) and 200 age- and sex-matched healthy controls were recruited. TNF-a and TNF-b genes were amplified using an amplification refractory mutation systems polymerase chain reaction methodology to detect TNF-α (–308) and -β (+252) polymorphisms. The frequency of the GA genotype of TNF-α (–308G/A) was higher, and the frequencies of the GG and AA genotypes were significantly lower in IBD patients compared with those in controls, indicating that genotype GA-positive individuals are susceptible to IBD and that the GG and AA genotypes exert a protective effect. The frequency of allele A of TNF-α (–308G/A) was significantly higher and that of allele G was lower in IBD patients compared with those in controls, indicating an association of allele A with IBD risk in Saudi patients. On stratification of IBD patients into UC and CD, an almost similar pattern was noticed in both the groups. The results of TNF-β (+252A/G) polymorphisms showed a significant increase in the frequency of the GG genotype in IBD patients, suggesting a positive association of GG genotype with IBD risk. On stratification of IBD patients into UC and CD, the genotype GG of TNF-β was associated with susceptibility risk to UC but not CD. The frequencies of alleles and genotypes of both TNF-α and-β polymorphisms are not affected by sex or type of IBD (familial or sporadic). TNF-α (–308G/A) and TNF-β (+252A/G) polymorphisms are associated with risk of developing IBD in Saudi population. Keywords: tumor necrosis factor, polymorphism, inflammatory bowel disease, Saudis, Crohn’s disease, ulcerative colitis